The regional and local party in light of the definition of a political party - Iwanek, Jan (Studia Politicae Universitatis Silesiensis, 2018)
Abstract: The regional and local party in light of the definition of a political party The author proposes a new concept of a political party, one which takes into account modern political groups active in local and regional communities. The stipulated definition is: a political party is a mass, distinct and formalized social group, which articulates group interests, acts based on a political program cohesive with social ideas, and achieves its aims in the execution of public authority by utilizing vertical central and territorial state institutions or relatively autonomous structures (territorial self-government, territorial autonomy, federal units). There is no need to create a separate definition of a regional and local party thanks to the proposed concept. The author does not share the position that a regional party is an ethnoregionalist party. It is submitted, that the political sciences understanding of a political party should differ from the legal view, and should not emphasize its legal status, but its functions and social roles. In this view, even trade unions, associations and even formalized groups of voters can be considered „parties”, if they actively and directly utilize public authority to achieve their group interests in the event of their election. Key words: regional party, local party, regional and local political party systems, decentralization